Abnormalities of pulmonary function and pleural disease among titanium metal production workers. - Garabrant, D H; Fine, Lawrence J; Oliver, C; Bernstein, L; Peters, J M (Scandinavian Journal of Work, Environment & Health, 1987)
The authors conducted a cross-sectional survey of respiratory disease among 209 titanium metal production workers. Work in areas where there was exposure to titanium tetrachloride and titanium dioxide particulates was associated with reductions in ventilatory capacity. Pleural disease (plaques and diffuse thickening) was present in the chest radiographs of 17% of the subjects and was associated with the duration of work in titanium manufacturing. It was also associated with past asbestos exposure. After control for asbestos exposure, it remained associated with titanium manufacturing. The findings are consistent with the hypothesis that titanium tetrachloride and titanium dioxide particulates may be associated with a reduction in ventilatory capacity and that the overall process of titanium manufacturing may be associated with unexpected pleural disease.